2016
DOI: 10.1371/journal.pntd.0004698
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro/In Vivo Model to Analyze the Effects of Flubendazole Exposure on Adult Female Brugia malayi

Abstract: Current control strategies for onchocerciasis and lymphatic filariasis (LF) rely on prolonged yearly or twice-yearly mass administration of microfilaricidal drugs. Prospects for near-term elimination or eradication of these diseases would be improved by availability of a macrofilaricide that is highly effective in a short regimen. Flubendazole (FLBZ), a benzimidazole anthelmintic registered for control of human gastrointestinal nematode infections, is a potential candidate for this role. FLBZ has profound and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Down-regulation of genes involved in early embryo morphogenesis may explain the apparent halt of embryogenesis associated with FLBZ exposure (O'Neill et al., 2016). Short-term in vitro exposure to FLBZ followed by long-term maintenance in vivo resulted in an increase in late morula stage embryos, the stage preceding the onset of elongation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Down-regulation of genes involved in early embryo morphogenesis may explain the apparent halt of embryogenesis associated with FLBZ exposure (O'Neill et al., 2016). Short-term in vitro exposure to FLBZ followed by long-term maintenance in vivo resulted in an increase in late morula stage embryos, the stage preceding the onset of elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to relatively high but pharmacologically relevant concentrations (10 μM) of FLBZ for 24 h was not lethal and worms were able to recover (O'Neill et al., 2015, O'Neill et al., 2016). These studies used histological techniques to assess tissues damage in an effort to determine a concentration range which may be lethal over this time-period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plates were incubated in a humid 5% CO 2 atmosphere at 37°C for 48 h and were observed under an inverted microscope at 2, 4, 6, 24, 30, and 48 h to count the dead worms. Parasites viability was estimated analyzing their motility and morphology, and they were classified into two categories: (0) dead; (1) alive, with normal morphology and varying degrees of motility [27]. The ABZ solution was used as the positive control and the culture medium with DMSO as the negative control.…”
Section: Dementioning
confidence: 99%
“…Different ways of assessing the state of worms in histological sections have been used. A scoring system that has been developed and used successfully for the investigation of new chemotherapeutic agents [11,12] and the type of degenerating forms seen in such studies shown…”
Section: Nematology -Concepts Diagnosis and Controlmentioning
confidence: 99%